التدخل الإنساني بين حماية حقوق الإنسان وانتهاك سيادة الدول - براح المداني (جامعة محمد بوضياف المسيلة, 2019)
يعد موضوع التدخل الإنساني من الموضوعات التي شغلت مساحة كبيرة بين الأوساط الدولية وذلك لأهميته وارتباطه بالتفاعلات التي تحدث في العلاقات الدولية،و لارتباطه بمواضيع مهمة في القانون الدولي كمبدأ عدم التدخل والسيادة وحقوق الإنسان، فهناك عددا من التعريفات التي تبيّن معنى هذا المصطلح وأنواعه، وكيفية التمييز فيما بينه وبين المفاهيم الأخرى القريبة منه،وتوضح الأصول التاريخية بهذا الموضوع انه ظهر على صعيد العلاقات الدولية قبل ظهور مبدأ عدم التدخل في الشؤون الداخلية للدول، وقد برز التدخل الإنساني في العقد الماضي بهد الحرب الباردة، كمحاولة لخلق الظروف المناسبة لإنشاء قواعد عرفية دولية جديدة، نخدم مصالح الدول التي نادت بإنشاء نظام دولي جديد، وذلك من خلال استغلال مبادئ حقوق الإنسان وقواعد القانون الدولي الإنساني بغية تبرير استخدام القوة بشكل غير قانوني، لتحقيق أهدافها السياسية والإستراتيجية. كما إن الإشكالية الأهم في الموضوع هو الخلاف في الرأي بين الباحثين والفقهاء حول شرعيته والآثار التي تنتج عنه على مبدأ سيادة الدول، تلك السيادة التي ظلت لعقود طويلة مقدسة لا يمكن المساس بها، حتى تغيرت الكثير من المفاهيم في العلاقات الدولية إلى درجة استحداث مبدأ جديد حل محل التدخل الإنساني سمي بمبدأ مسؤولية الحماية لتجد الدول نفسها تتجه نحو السيادة النسبية أو المحدودة، وتتخلى عن جزء من سيادتها لصالح سيادة المجتمع الدولي والتحول من السيادة كسيطرة إلى السيادة كمسؤولية. Abstract: The subject of humanitarian intervention is one of the topics that occupied a large area among the international community because of its importance and its relevance to the interactions that take place in international relations and its relevance to important subjects in international law such as the principle of non-intervention, sovereignty and human rights. There are a number of definitions that show the meaning of this term and its types, As well as the other concepts close to it. The historical origins of this subject show that it appeared at the level of international relations before the emergence of the principle of non-interference in the internal affairs of states. The humanitarian intervention in the past decade has emerged in the Cold War, In order to establish new international customary rules, we serve the interests of States that have advocated the establishment of a new international order by exploiting the principles of human rights and the rules of international humanitarian law to justify the illegal use of force to achieve their political and strategic objectives. The most important problem is the difference of opinion between researchers and scholars on the legitimacy and effects that result from the principle of sovereignty of States, which has remained for decades sacred and can not be touched, even changed a lot of concepts in international relations to the point of creating a new principle solution The place of humanitarian intervention is called the principle of the responsibility of protection to find States themselves moving towards relative or limited sovereignty, abandoning part of their sovereignty in favor of the sovereignty of the international community and the transition from sovereignty to sovereignty as responsibility.
Keywords: التدخل الانساني، مسؤولية الحماية، سيادة الدول، انتهاك السيادة، السيادة كمسؤولية